2007
DOI: 10.1634/stemcells.2006-0479
|View full text |Cite
|
Sign up to set email alerts
|

IMT504, the Prototype of the Immunostimulatory Oligonucleotides of the PyNTTTTGT Class, Increases the Number of Progenitors of Mesenchymal Stem Cells Both In Vitro and In Vivo: Potential Use in Tissue Repair Therapy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…IMT504 (Oligos Etc., Wilsonville, OR, USA) was treated as described [5], its sequence being 5′-TCATCATTTTGT CATTTTGTCATT-3′.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IMT504 (Oligos Etc., Wilsonville, OR, USA) was treated as described [5], its sequence being 5′-TCATCATTTTGT CATTTTGTCATT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas CpG ODNs have been evaluated in autoimmune diseases [1], no data are available regarding IMT504. Interestingly, while IMT504 is a potent stimulator of mesenchymal stem cells (MSCs), CpG ODNs are not [5]. We have shown that IMT504 is useful for tissue repair in a bone injury model [5], presumably through expansion of the MSC pool and/or modifications in the immunochemical microenvironment at the site of damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phosphorothioate (PS) CpG ODNs induce the secretion of IFN alpha [8], while PS PyNTTTTGT ODNs do not [9], and PyNTTTTGT ODNs induce the release of GM-CSF acting on human NK and NKT cells in the presence of IL-2, while CpG ODNs do not (our unpublished data). Furthermore, PyNTTTTGT ODNs stimulate in vitro and in vivo the expansion of mesenchymal stem cell precursors while CpG ODNs do not [10]. Here, we report that IMT504, the prototype of the PyNTTTTGT class, provides a highly significant survival advantage after a lethal rabies challenge in a rat model, even with large dilutions of the rabies vaccine.…”
Section: Introductionmentioning
confidence: 85%
“…Titers of anti-rabies glycoprotein antibodies have been reported to have a reasonable correlation with the titers of serum neutralizing antibodies measured by the rapid fluorescent focus inhibition test (RFFIT), which is currently accepted as the gold standard technique [13][14][15]. Table 1 shows that after the second injection, all of the individuals in the IMT504 group reached protective levels (>0.5 IU/ml) as defined by the WHO [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Notably, four out of five reached levels 60 -90 times higher than the required protective level after the third dose.…”
Section: Immunization Of Human Volunteers With Vero Cell Rabies Vaccimentioning
confidence: 99%